Asymptotic Values of Entire Functions of Infinite Order - Hinkkanen, Aimo; Miles, Joseph (Computational methods and function theory, 2023)
We prove that there exists an entire function for which every complex number is an asymptotic value and whose growth is arbitrarily slow subject only to the necessary condition that the function is of infinite order.